2015
DOI: 10.1111/ijsa.12101
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Applicants' and Incumbents' Mean Scores on Health Constructs and Personality Constructs. A Follow‐up Study of Military Recruits in a Selection Setting

Abstract: This study investigated the change in means on both personality constructs and the more infrequently studied, health constructs, as a possible effect of self‐enhancement in a real selection setting. The participants (N = 202) were assessed first as applicants, and later as incumbents. The result revealed that, while all the means for personality constructs changed across situations, the effect sizes on the health constructs were stronger. The analysis also revealed that it was twice as likely for the incumbent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 56 publications
(113 reference statements)
0
3
0
Order By: Relevance
“…This is a view that is based on a few research studies that seem to have shown that applicants or incumbents responded to a test in very similar ways, for example, Hogan, Barrett and Hogan (). These results are exceptional, because extensive research has shown that applicants and incumbents differ strongly, not only in personality tests but probably in all contexts perceived to be value relevant, such as reported health status (Bäccman, Sjöberg & Almqvist, in press).…”
Section: Discussionmentioning
confidence: 99%
“…This is a view that is based on a few research studies that seem to have shown that applicants or incumbents responded to a test in very similar ways, for example, Hogan, Barrett and Hogan (). These results are exceptional, because extensive research has shown that applicants and incumbents differ strongly, not only in personality tests but probably in all contexts perceived to be value relevant, such as reported health status (Bäccman, Sjöberg & Almqvist, in press).…”
Section: Discussionmentioning
confidence: 99%
“…Because modesty values are stronger in Eastern cultures than Western cultures (Heidemeier & Moser, 2009; Heine & Hamamura, 2007), self‐presentation behaviors in Eastern cultures are likely to be compressed downwards, that is, uniformly low. Because the variance in self‐presentation is low in Eastern cultures, there is little covariance between self‐presentation and the traits that are typically used to predict it (e.g., trait CSE, narcissism; Bäccman et al, 2015; García et al, 2009; Morf et al, 2010; Paulhus et al, 2013). Applicants from Eastern cultures, no matter how high their CSE, will be less inclined to spend time in a cover letter or interview highlighting their qualifications and past successes because self‐presentation is viewed negatively.…”
Section: Rv Weirdness and Selection And Assessmentmentioning
confidence: 99%
“…cultures than Western cultures (Heidemeier & Moser, 2009;Heine & Hamamura, 2007), self-presentation behaviors in Eastern cultures are likely to be compressed downwards, that is, uniformly low. Because the variance in self-presentation is low in Eastern cultures, there is little covariance between self-presentation and the traits that are typically used to predict it (e.g., trait CSE, narcissism; Bäccman et al, 2015;García et al, 2009;Morf et al, 2010;Paulhus et al, 2013).…”
Section: How Rv Interactions Work: a Weird Illustrationmentioning
confidence: 99%